1994
DOI: 10.1161/01.atv.14.12.1958
|View full text |Cite
|
Sign up to set email alerts
|

Three novel mutations of antithrombin inducing high-molecular-mass compounds.

Abstract: We have identified three novel mutations of the antithrombin (AT) gene in patients with thrombotic complications: a Cys 128 -» Tyr mutation, a G -» A mutation in the intervening sequence 4 (FVS4) 14 nucleotide 5' to exon 5, and a 9 bp deletion in the 3' end of exon 6 resulting in a short aberrant sequence after Arg 425. The latter mutation was associated with an Arg 47 -• His mutation in two compound heterozygous brothers. These three mutations led to the expression in the circulation of small amounts of inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…Unlike the classical type I variants that result from major deletions or the presence of premature stop codons, the conformational variants are secreted into the plasma, albeit as here, the variants form only 5–15% of the circulating antithrombin. One recognized disadvantageous consequence is the conversion of such unstable antithrombins to the latent conformation [9,20,24], with an accompanying inactivation of the functionally normal component [25]. However, the variants reported here do not appreciably undergo the latent transition, but rather the prime finding is the presence in the plasma of dimers of the variant antithrombin.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike the classical type I variants that result from major deletions or the presence of premature stop codons, the conformational variants are secreted into the plasma, albeit as here, the variants form only 5–15% of the circulating antithrombin. One recognized disadvantageous consequence is the conversion of such unstable antithrombins to the latent conformation [9,20,24], with an accompanying inactivation of the functionally normal component [25]. However, the variants reported here do not appreciably undergo the latent transition, but rather the prime finding is the presence in the plasma of dimers of the variant antithrombin.…”
Section: Discussionmentioning
confidence: 96%
“…In the case of type I deficiency, AT (E⌬313) and AT (P429Stop) are degraded rapidly by proteasomes when these cDNAs are expressed in baby hamster kidney cells (40). The mutations AT (C128Y) and AT (C430F) were identified recently (41,42), but the intracellular fate of these ATs has not yet been elucidated. From our investigation, these ATs are likely to have a similar intracellular fate as AT (C95R).…”
Section: Discussionmentioning
confidence: 99%
“…Emmerich et al reported that loss of an intramol ecular disulfide bond of AT could induce high-molecu lar-weight compounds and the pleiotropic phenotypes by partial misfolding and the formation of intermolecular disulfide bonds with other components in plasma. 9 How ever, we could not detect a variant molecule or a highmolecular-mass compound in the affected plasmas by immunoblotting.…”
Section: Discussionmentioning
confidence: 93%